TA

hỏi bạn

(x+3)*(x^2-3x+5)=x^2+3x 

làm như thế nào vậy !!

 

ER
25 tháng 10 2017 lúc 18:51

(x+3)(x2-3x+5)=x2+3x

=>(x+3)(x2-3x+5)-x(x+3)=0

=>(x+3)(x2-3x+5-x)=0

=>(x+3)(x2-2x+5)=0

\(\Rightarrow\orbr{\begin{cases}x+3=0\\x^2-2x+5=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-3\\\left(1\right)\end{cases}}\)      vậy x=-3

xét vế (1)

x2-2x+5=0

=>(x-1)2+4=0

do (x-1)2\(\ge\)0

\(\Rightarrow\left(x-1\right)^2+4>0\)

vậy vế  vô nghiệm

Bình luận (0)
NT
25 tháng 10 2017 lúc 18:55

sao kì vậy?

(x+3).(x2-3x+5)=x3-3x2+5x+3x2-9x+15=x3-4x

Làm thế này mới đúng

Bình luận (0)

Các câu hỏi tương tự
H24
Xem chi tiết
PB
Xem chi tiết
HL
Xem chi tiết
H24
Xem chi tiết
HT
Xem chi tiết
V2
Xem chi tiết
HT
Xem chi tiết
AM
Xem chi tiết
Xem chi tiết